A Review of Foreign Experiences in Implementing Budget Policy in Inter-Budgetary Relations - Zaichko, I. V. (Statistics of Ukraine, 2018)
The article investigates the theoretical and methodological framework of foreign experiences in implementing budget policy in inter-budgetary relations. It is demonstrated that the model of inter-budgetary relations, existing in Ukraine, does not contribute in creating necessary incentives for local governments to ensure appropriate management of budgets. The situation can be improved only by harmonizing the reform of inter-budgetary relations with the general logic of change in regional relations. It is demonstrated that the use of income differentiation method depends on the structural basis of the budget system, which is determined by the organization of the State. While in unitary countries taxes are most often split with fixed rates and allowances to national taxes, in federal countries distribution of income between budgets is used. As foreign experiences show, while in federal countries optimal mobilization and socially oriented spending of budget funds requires a long time, in unitary countries it can be possibly done in a relatively short time, but it needs clearly defined social goals and ways to achieve them. In the budgetary practice of Ukraine two methods of budget regulation are used: (i) deductions from national taxes and incomes collected on local budget territories; (ii) fixed financial assistance to local budgets in form of budget transfers. The advantages of the first method are balancing of local budgets by use of flexible revenue sources, local governments’ concern with full mobilization of not only local revenue sources, but also national taxes, the responsibility of local financial authorities for timely and complete receipt of national taxes. Budget regulation does not exclude the possibility of using budget transfers. The review of foreign experiences in local budgeting shows that the budget regulation instruments practiced in unitary countries would be useful for Ukraine.